2019
DOI: 10.1038/s41598-019-40535-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of nonlinear receptive fields of visual neurons by convolutional neural network

Abstract: A comprehensive understanding of the stimulus-response properties of individual neurons is necessary to crack the neural code of sensory cortices. However, a barrier to achieving this goal is the difficulty of analysing the nonlinearity of neuronal responses. Here, by incorporating convolutional neural network (CNN) for encoding models of neurons in the visual cortex, we developed a new method of nonlinear response characterisation, especially nonlinear estimation of receptive fields (RFs), without assumptions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…We visualized the preferred features of neurons in CNNs trained with the modified database using the DeepDream response-maximization approach [78]. This analysis indicated that neurons in early layers developed circular receptive fields (RFs) reminiscent of retinal ganglion and LGN cells; in deeper layers, they resembled oriented RFs akin to both simple and complex cells (S5 Fig), as previously reported, e.g., [59,[79][80][81][82]. Paralleling stimulation protocols typically used in experimental recordings in visual areas, we then examined CNNs responses to oriented gratings.…”
Section: Visual Stability During Saccadic Eye Movementsmentioning
confidence: 69%
“…We visualized the preferred features of neurons in CNNs trained with the modified database using the DeepDream response-maximization approach [78]. This analysis indicated that neurons in early layers developed circular receptive fields (RFs) reminiscent of retinal ganglion and LGN cells; in deeper layers, they resembled oriented RFs akin to both simple and complex cells (S5 Fig), as previously reported, e.g., [59,[79][80][81][82]. Paralleling stimulation protocols typically used in experimental recordings in visual areas, we then examined CNNs responses to oriented gratings.…”
Section: Visual Stability During Saccadic Eye Movementsmentioning
confidence: 69%
“…An important milestone towards this goal is to achieve general system identification models that can predict the response of large populations of neurons to arbitrary visual inputs. In recent years, deep neural networks have set new standards in predicting responses in the visual system (Yamins et al, 2014; Vintch et al, 2015; Antolík et al, 2016; Cadena et al, 2017; Batty et al, 2016; Kindel et al, 2017; Klindt et al, 2017; Zhang et al, 2018; Ecker et al, 2018; Sinz et al, 2018) and the ability to yield novel response characterizations (Walker et al, 2019; Bashivan et al, 2019; Ponce et al, 2019; Kindel et al, 2019; Ukita et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By calculating the area under the curve (AUC) of the receiver operating characteristic curve using 5-fold cross-validation (DuBrava et al, 2017; Le et al, 2019b; Le, Ho & Ou, 2017; Ukita, Yoshida & Ohki, 2019), we performed feature selection and hyperparameters optimization to determine the models. Calculation of AUC was performed using an R library named ‘ROCR’ (version 1.0.7).…”
Section: Methodsmentioning
confidence: 99%